2003
DOI: 10.1007/s10151-003-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding, incontinence, pain and constipation after STARR transanal double stapling rectotomy for obstructed defecation

Abstract: Parity, spastic floor syndrome and psychoneurosis seem to be the risk factors predisposing to failure of DSP, which may be followed by severe complications and early recurrence of symptoms requiring reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
2
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 17 publications
5
95
2
8
Order By: Relevance
“…9,10,20,21 Immediate postoperative complications were mainly related to cases of bleeding from the staple line, similar to what occurred in previously reported series. [21][22][23] Considering that a fullthickness segment of the rectal wall is excised, it is surprising that pelvic sepsis was not encountered in any of our patients, confirming previous reports. 9,20 Gagliardi et al 21 reported sepsis complicating 3.5% of their 85 STARRs; all three cases resolved with a combination of intravenous antibiotics and/or transanal drainage.…”
Section: Discussionsupporting
confidence: 77%
“…9,10,20,21 Immediate postoperative complications were mainly related to cases of bleeding from the staple line, similar to what occurred in previously reported series. [21][22][23] Considering that a fullthickness segment of the rectal wall is excised, it is surprising that pelvic sepsis was not encountered in any of our patients, confirming previous reports. 9,20 Gagliardi et al 21 reported sepsis complicating 3.5% of their 85 STARRs; all three cases resolved with a combination of intravenous antibiotics and/or transanal drainage.…”
Section: Discussionsupporting
confidence: 77%
“…22,[33][34] These conflicting observations are explained by the limited clinical use of STARR, as the literature accounts for fewer than 400 patients. These patients were recruited by different institutions that lack not only uniform inclusion/exclusion criteria but also expertise in stapler-assisted transanal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there was a low bleeding rate (3%) compared with previous reports (4 -12%). [17][18][33][34] The proper use of a retractor and vaginal valve avoided any entrapment of adjacent viscera, mostly of the posterior wall of vagina, thus avoiding the risk of rectovaginal fistula. Few patients (3%) had gauze tampons intra-anally inserted when the operation was concluded, thus reducing the rate of postoperative urinary retention (5.6 -12% in previous reports).…”
Section: Discussionmentioning
confidence: 99%
“…All patients had signifi cant improvement in constipation symptoms without affecting continence, and postoperative defaecating proctography showed the disappearance of both the intussusception and rectocele [ 17 ]. Severe complications, however, have been reported, including bleeding, faecal urgency, incontinence, stenosis, dramatic chronic pain, constipation [ 38 ] and rectovaginal and enteral fi stulas [ 39 , 40 ].…”
Section: Type I Digitiform Rectocele or Single Hernia Through The Recmentioning
confidence: 99%